Electrical characteristics and Thermoelectric Properties of LaZnSbO - Liu, Jian (International Journal of Materials Science and Technology Studies, 2026)
Using density functional theory calculations, the thermoelectric properties of LaZnSbO have been systematically investigated. The bulk LaZnSbO features a natural super lattice structure with low electrical conductivity and low thermal conductivity. The band structure reveals that it is a direct gap semiconductor having a band gap of 0.73eV. Doping can enhance its conductivity and thereby raise its ZT value. At a temperature of 900K, close to the carrier concentration 2.5×1019/cm3, the p-type doped system shows a Seebeck coefficient of 313μVκ-1, a conductivity of 2.06×104Sm-1 and a power factor of 0.78×10-3Wm-1κ-2. As a result, a thermoelectric figure of merit (ZT) reaches a maximum value of 1.43.